Activated mitochondrial dynamin-related protein 1 couples with LRRK2 to cause mitochondrial dysfunction in hypoxic cells - DUAN Chenyang (Di-san junyi daxue xuebao, 2020)
Objective To explore the mechanism of activated mitochondrial dynamin-related protein 1 (Drp1) in regulating mitochondrial energy metabolism and aerobic respiration after hypoxia. Methods We observed the changes of Drp1 activity and its relationship with mitochondrial damage by coimmunoprecipitation and immunofluorescence in cardiac myocyte line H9C2, vascular smooth muscle cells (VSMCs) and intestinal epithelial cells (IECs). The protein interaction model of Drp1 and LRRK2 was established using ZDOCK and verified by coimmunoprecipitation. A point mutation (T595A) was introduced in Drp1 gene to disrupt the coupling of Drp1 and LRRK2 in VSMCs, and the acidification of the culture medium, extracellular lactate content, mitochondrial membrane potential and ATP production of the cells were examined. Results Hypoxia caused significantly increased level of Thr phosphorylation in Drp1 and obvious mitochondrial damage in the cells. After hypoxia, numerus hydrogen bonds were found between the interface residues of Drp1 and LRRK2 proteins, which resulted in close binding between them to cause mitochondrial dysfunction, manifested by an increased lactate production during glycolysis and a decreased mitochondrial membrane potential during mitochondrial aerobic respiration. Conclusion Activated Drp1 causes impairment of mitochondrial energy metabolism and aerobic respiration by coupling with LRRK2 to aggravate mitochondrial damage in multiple tissues and organs after hypoxia.